Brain transcriptome analysis of a CLN2 mouse model as a function of disease progression - Miriam S. Domowicz; Wen-Ching Chan; Patricia Claudio-Vázquez; Tatiana Gonzalez; Nancy B. Schwartz (Journal of Neuroinflammation, 2021)
Abstract Background Neuronal ceroid lipofuscinoses, (NCLs or Batten disease) are a group of inherited, early onset, fatal neurodegenerative diseases associated with mutations in 13 genes. All forms of the disease are characterized by lysosomal accumulation of fluorescent storage material, as well as profound neurodegeneration, but the relationship of the various genes’ function to a single biological process is not obvious. In this study, we used a well-characterized mouse model of classical late infantile NCL (cLINCL) in which the tripeptidyl peptidase 1 (Tpp1) gene is disrupted by gene targeting, resulting in loss of detectable TPP1 activity and leading to progressive neurological phenotypes including ataxia, increased motor deficiency, and early death. Methods In order to identify genes and pathways that may contribute to progression of the neurodegenerative process, we analyzed forebrain/midbrain and cerebellar transcriptional differences at 1, 2, 3 and 4 months of age in control and TPP1-deficient mice by global RNA-sequencing. Results Progressive neurodegenerative inflammatory responses involving microglia, astrocytes and endothelial cells were observed, accompanied by activation of leukocyte extravasation signals and upregulation of nitric oxide production and reactive oxygen species. Several astrocytic (i.e., Gfap, C4b, Osmr, Serpina3n) and microglial (i.e., Ctss, Itgb2, Itgax, Lyz2) genes were identified as strong markers for assessing disease progression as they showed increased levels of expression in vivo over time. Furthermore, transient increased expression of choroid plexus genes was observed at 2 months in the lateral and fourth ventricle, highlighting an early role for the choroid plexus and cerebrospinal fluid in the disease pathology. Based on these gene expression changes, we concluded that neuroinflammation starts, for the most part, after 2 months in the Tpp1 −/− brain and that activation of microglia and astrocytes occur more rapidly in cerebellum than in the rest of the brain; confirming increased severity of inflammation in this region. Conclusions These findings have led to a better understanding of cLINCL pathological onset and progression, which may aid in development of future therapeutic treatments for this disease.